1) выполнить действия: 3y² (y³ +1) ; (3a - 4ax +2) - (11a - 14ax) . 2) вынесите общий множитель за скобку: 3x² +9xy ; 10x⁵ - 5х3) 3) решите уравнение: 4(х +1) = 15х -7 (2х +5)

cooldude28 cooldude28    2   18.05.2019 09:50    3

Ответы
vanyadrachuk2004 vanyadrachuk2004  11.06.2020 16:04

1) 3y^2  (y^3 +1)= 3y^6+3y^2

     (3a - 4ax +2) - (11a - 14ax) = 3a-4ax+2-11a+14ax= 10ax-8a+2

2) 3x^2 +9xy= 3x (x+3y)

     10x^5 - 5х^3= 5x^3 (2x^2-1)

3) 4(х +1) = 15х -7 (2х +5)

      4x+4= 15x-14x-35

      4x-15x+14x+4+35=0

       3x+39=0   | :3

       x+ 13=0

       x= -13

      ответ: -13

     

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра